Romantic Recognition: A theoretical revision of love in Axel Honneth's "The Struggle for Recognition" - Stouby Andersen,Amalie (2025)
In Axel Honneth's "The Struggle for Recognition" (1995), love as mutual recognition is dealt with through the psychoanalytic theory of Donald Winnicott, who focused principally on relations between parents and their young children. Consequently, Honneth's conceptualisation of love is ill-suited for application in the study of late modern adult romantic relationships. In this thesis, I argue that this is problematic for a normative theory of recognition, and I therefore propose a new conceptualisation of love which is better suited for the critical analysis of romantic recognition in a late modern culture of love. After presenting Honneth’s theory in full and foregrounding a few of the main issues of his conceptualisation of love, I argue that the ideals of self-realisation and autonomy are central challenges in the contemporary culture of love, as they fundamentally alter our ideas and thoughts of dependence. I explore the three stages of the development of recognition as love – symbiosis, struggle, and finally love – as they are experienced in adulthood, with a particular focus on how the struggle might be intensified by the presence of the above-mentioned ideals. Finally, I develop a new conceptualisation of love which is compatible with the remaining parts of Honneth’s theory, but which places a greater emphasis on the importance of human interdependence as well as the possibility and consequences of a denial of love in adulthood.
Keywords: Love; recognition; The Struggle for Recognition; Axel Honneth; romantic relationships; late modernity; commitment